NURSING PROFESSIONALS AND ADVERSE EVENT REPORTING - Maldonado, Ximena Alejandra Navarro; Nascimento, Eliane Regina Pereira do; Lazzari, Daniele Delacanal (My University, 2020)
ABSTRACT Objective: to identify how nurses report adverse events; to know what elements influence adverse event reporting and which reporting strategies they suggest. Method: qualitative study with a convergent care research design, conducted in a critical patient unit of a private health center in the region of Magallanes, Chile. Thirteen nurses participate in the study, through interviews and a discussion group. Results: the nurses who report adverse events do so verbally and in writing to the nurse coordinator immediately. Failure to report adverse events is mainly due to lack of knowledge of the safety culture, fear of reprisals and punishment within the workplace. As adverse event reporting strategies, they suggest continuing education about the safety culture, raising awareness and trust in that error reporting will not be met with punishment and that the error will lead to an improvement plan that avoids committing the same error on another occasion, improving communication and leadership. Conclusion: although nurses report adverse events, they are concerned with punishment, indicating the need to review the patient safety culture at a critical care unit in the study context.
Keywords: nursing; intensive care units; patient safety; notification; nursing staff